Diversification and professionalization in psychology - Pléh, Csaba, author.
1 online resource.
Keywords: "Diversification and Professionalization in Psychology offers readers a multicentric perspective on the history of social science and compares the developments in psychology in relation to the developments made in the other social and natural sciences"--